2017
DOI: 10.1371/journal.pone.0177748
|View full text |Cite
|
Sign up to set email alerts
|

Migratory bats respond to artificial green light with positive phototaxis

Abstract: Artificial light at night is spreading worldwide at unprecedented rates, exposing strictly nocturnal animals such as bats to a novel anthropogenic stressor. Previous studies about the effect of artificial light on bats focused almost exclusively on non-migratory species, yet migratory animals such as birds are known to be largely affected by light pollution. Thus, we conducted a field experiment to evaluate if bat migration is affected by artificial light at night. In late summer, we presented artificial green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 47 publications
(42 reference statements)
7
35
0
2
Order By: Relevance
“…The observed orientations would lead bats southwards and back to the flyway along the dunes of the shoreline. Based on our findings combined with previous results about population genetics, phenological occurrences and flight behaviour at sea sides, we argue that P. pygmaeus can be considered a true migratory species, at least in northern parts of its distribution range (Ahlén et al ., ; Sztencel‐Jabłonka & Bogdanowicz, ; Rydell et al ., ; Voigt et al ., , ). Quantitative studies based on tagged individuals are now needed to evaluate how regular P. pygmaeus migrate over longer distances and where individuals of northern populations are overwintering.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed orientations would lead bats southwards and back to the flyway along the dunes of the shoreline. Based on our findings combined with previous results about population genetics, phenological occurrences and flight behaviour at sea sides, we argue that P. pygmaeus can be considered a true migratory species, at least in northern parts of its distribution range (Ahlén et al ., ; Sztencel‐Jabłonka & Bogdanowicz, ; Rydell et al ., ; Voigt et al ., , ). Quantitative studies based on tagged individuals are now needed to evaluate how regular P. pygmaeus migrate over longer distances and where individuals of northern populations are overwintering.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…Here, we focused on the orientation behaviour of individual P. pygmaeus caught between August and September at Pape Bird Ringing Station (PBRS) at the Latvian Baltic Sea coast. Previous acoustic studies demonstrated a regular occurrence of the species at PBRS during summer migration (Rydell et al ., ; Voigt et al ., , ), yet it is unknown if this reflects the seasonal occurrence of P. pygmaeus in this region without pronounced directional migration flights. Interestingly, similar to other bats passing PBRS on migration, P. pygmaeus only exceptionally displays foraging behaviour (Voigt et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all previous studies focused on bats during the nonmigration period. In the first study on migratory bats, Voigt, Roeleke, Marggraf, Pētersons, and Voigt‐Heucke () showed that bats are attracted to green light when migrating. Specifically, Voigt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used the same experimental setup at the migration corridor in Latvia as described by Voigt et al. (), but switched the light source from green wave length spectra to LED emitting light in the red and white spectrum. The wavelength composition in the red spectrum was similar to conventional red aviation light installed globally (Breckenridge, ).…”
Section: Introductionmentioning
confidence: 99%